A new species of Fissiphalliidae from Brazilian Amazon Rain Forest (Arachnida: Opiliones) - Pinto-Da-Rocha, Ricardo (Zootaxa, 2004)
The fourth species of the family Fissiphalliidae is described, Fissiphallius martensi new species, from Reserva Ducke, Manaus, Amazonas, Brazil. It differs from other 3 species of the family by having ventral plate sword-like, sulcus II straight, the presence of a high spine on the eye mound, spines on coxa IV, lateral margin of dorsal scute, tergites, anal operculum and sternites, and the genital operculum shorter than stigmatic area.